Social emotional skills (SES) among lecturers in relation students performance - Dahri, Salma (2018)
Social emotional skills (SES) of a lecturer are considered to play a vital role towards student performance. Despite of the fact, when it comes to Technical Vocational Education and Training (TVET), very little research is found on the importance and implementation of these skills. This research therefore determined the level of TVET lecturers’ SES based on lecturers’ and students’ perspective, their relationship with student performance and difference in the level of SES between lecturers in education faculty and in engineering faculty. A case study method with quantitative approach was employed at Universiti Tun Hussein Onn Malaysia (UTHM). A total of 99 lecturers and 373 of final year bachelor degree students from an education and an engineering faculties were involved in this study. They were selected using purposive sampling and total population sampling techniques. Data were collected using two sets of questionnaire, Empathy Quotient (EQ) to measure empathy and Teacher Interpersonal Self-efficacy Scale to measure self-efficacy. Findings showed that lecturers have high level of SES from lecturers’ and students’ perspective. Furthermore, the results of Mann Whitney U Test indicated statistically significant difference the perspective of lecturers and students. However, there was no significant correlation between lecturers’ SES with students’ performance. Nonetheless, lecturers’ self-efficacy for classroom management had statistically significant relationship with students’ performance. Meanwhile, there was also significant difference found in the level of lecturers’ social emotional skills between both faculties. It is concluded that external related reliable feedback is important for lecturers to get to know about their level of SES. SES have a vital role towards students’ performance and that lecturers with professional education background are more effective than lecturers with engineering background. It is hoped that this study could enhance the awareness of TVET institutions in SES as such could help the development of better skill workers in future.